PlantACT! – how to tackle the climate crisis. (May 2023) - Hirt, Heribert; Al-Babili, Salim; Almeida-Trapp, Marilia; Martin, Antoine; Aranda, Manuel; Bartels, Dorothea; Bennett, Malcolm; Blilou, Ikram; Boer, Damian; Boulouis, Alix; Bowler, Chris; Brunel-Muguet, Sophie; et al.
Highlights: Agriculture contributes to global climate change by producing 20–25% of greenhouse gases (GHGs). CO2 is released from deforestation and land conversion, methane from rice paddy fields, and nitrous oxides from overfertilization. An increasing world population requires a change in the agro food systems, including a reduction in chemical fertilizers and pesticides as well as the production and access to food. Abstract: Greenhouse gas (GHG) emissions have created a global climate crisis which requires immediate interventions to mitigate the negative effects on all aspects of life on this planet. As current agriculture and land use contributes up to 25% of total GHG emissions, plant scientists take center stage in finding possible solutions for a transition to sustainable agriculture and land use. In this article, the PlantACT! (Plants for climate ACTion!) initiative of plant scientists lays out a road map of how and in which areas plant scientists can contribute to finding immediate, mid-term, and long-term solutions, and what changes are necessary to implement these solutions at the personal, institutional, and funding levels.